PENGARUH PEMANFAATAN TEH BUNGA ROSELA TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Sumirat, Widhi (Jurnal AKP, 2012)
Hypertension is a persistent increase in blood pressure above normal limits agreed upon, namely 90 mm Hg diastolic or 140 mmHg systolic. Hypertension can be treated with modern medicine and traditional medicine. One of the traditional medicine that can be used is rosella flower tea. Many people who believe that the efficacious rosella flower tea to lower blood pressure, but the utilization of rosella flower tea for lowering blood pressure in hypertensive patients in Indonesia is still lacking. The purpose of this study is to investigate the influence utilization of rosella flower tea to the reduction of blood pressure in hypertensive patients. This research design is experimental quasy two groups: the study group and control group, using the approach of the pre and post. Hypertensive population is all degree one. The sample of this research are about 18 people, nine were treated and 9 control. Data analysis was done by comparing the blood pressure level before and after treatment, inferential analyzed to determine the mean and standard defiasi.Results from the study showed that the treatment group decreased from 143.89 mmHg systole pressure to 128.78 mm Hg or a decrease of 10.5%. While the diastole pressure from 93.89 mmHg to 81.22, down 13.5%. From the description above we can conclude that there is a decrease in blood pressure in the group given rosella flower tea for 12 days in a row, means proven rosella flower tea can lower blood pressure in hypertensive patients.